Sodium Intake Is Associated With Renal Resistive Index in an Adult Population-Based Study. Issue 6 (December 2020) - Jaques, David A.; Pruijm, Menno; Ackermann, Daniel; Vogt, Bruno; Guessous, Idris; Burnier, Michel; Pechere-Bertschi, Antoinette; Bochud, Murielle; Ponte, Belen
Abstract : Renal resistive index (RRI) has been associated with adverse renal and cardiovascular outcomes. Although traditionally considered a marker of intrinsic renal damage, RRI could also reflect systemic vascular dysfunction. As sodium intake was linked to alterations in vascular properties, we wished to characterize the association of salt consumption with RRI in the general adult population. Participants were recruited in a population-based study in Switzerland. RRI was measured by ultrasound in 3 segmental arteries. Sodium intake (UNa; mmol/24 h) was estimated on 24-hour urine samples. Carotido-femoral pulse wave velocity was obtained by applanation tonometry. Mixed multivariate regression models were used with RRI or pulse wave velocity as independent variables and UNa as dependent variable, adjusting for possible confounders. We included 1002 patients in the analyses with 528 (52.7%) women and mean age of 47.2±17.4. Mean values of UNa and RRI were 141.8±61.1 mmol/24 h and 63.8±5.5%, respectively. In multivariate analysis, UNa was positively associated with RRI ( P =0.002) but not with pulse wave velocity ( P =0.344). Plasma renin activity and aldosterone did not modify the relationship between UNa and RRI ( P =0.087 for interaction). UNa/urinary potassium ratio was positively associated with pulse wave velocity ≥12 m/s ( P =0.033). Our results suggest that dietary salt consumption has a direct impact on renal hemodynamic in the adult general population. Alterations in vascular properties likely explain those findings, but inadequate renal vaso-motor response is also possible. Sodium intake could thus potentially be linked to underlying structural systemic damages affecting this population. Abstract : Supplemental Digital Content is available in the text.